Effect of different attacks on image watermarking using dual tree complex wavelet transform (DTCWT) and principle component analysis (PCA) - Sudha, M S; Thanuja, T C (International Journal of Engineering & Technology, 2018)
Perceptibility and robustness are two incongruous requirements demanded by digital image watermarking for digital right management and other applications. A realistic way to concurrently satisfy the two contradictory requirements is to use robust watermark algorithm. The developed algorithm uses DTCWT and PCA techniques to embed watermark signal in host signal. To prove the algorithm robustness without much affecting perceptibility several attacks like noises, cropping, blurring, rotation are applied and tested by varying attack parameters. Parameters like Peak signal noise ratio and Correlation Coefficient are calculated for each attack. Attack percentage is varied and performance parameters are calculated to prove the robustness of the developed algorithm.